Leisure Activities as a Driver for the Development of Libraries in the Modern World - G. L. Ruksha; I. A. Sheremetova (Библиосфера)
Social, economic, political, digital transformations in society lead to changes in Russian social and cultural space. Leisure becomes a significant part of the modern cultural process. The problem of the study of cultural and leisure activities (CLA) remains open. Leisure activities are undergoing changes. The article provides an empirical analysis of cultural and leisure activities to comprehend the current stage of the cultural development process in Russia. The authors give the examples of the dependence of the forms of library practice on changing reader needs in a historical retrospective. It is noted that various forms of CLA are commonly implemented into the work of cultural institutions. Intellectual and leisure activities becomes a significant part of CLA. It is necessary for the inclusion of an individual into modern educational, professional, cultural spaces. New digital combined forms of work and project activities are popular tools that increase efficiency of cultural and leisure activities of cultural institutions. The article provides examples of the active involvement of the State Universal Scientific Library of Krasnoyarsk region in the intellectual leisure industry. The authors come to the conclusion that the content and technological change of CLA as a systemic phenomenon occurs under the influence of the realities of modern life and contributes to the functions evolution in cultural institutions.